Application of English Language Learning to Children Based on Digital Media - Mulyadi, Ahmad Iman; Putri, Intan; Puspita, Hilda (Journal of English Education and Teaching, 2024)
Digital-based learning is carried out to help the process of English communication interaction between teachers and students. To achieve learning goals and increase learning outcomes. Teachers must be able to develop ideas in creating learning media. In this case, the use of digital-based learning media such as using animated video images and audio as intermediaries to convey learning material. This research describes how to apply digital media-based English language learning to children. The research method is qualitative research by conducting interviews, observation and documentation. The research results show that digital learning media can increase children's participation in learning English. Attractive digital-based learning media can empower children and develop children's imagination when learning English. In this case, it can be concluded that learning English by applying digital media as a learning medium can increase children's participation, however there are several challenges related to access and digital skills of teachers that need to be improved to optimize the English teaching process